Fermentation Profile and Nutrient Composition of Rehydrated Dry Mesquite Pod (Prosopis spp.) Silage with Increasing Moisture Levels - Granados-Niño, J. A.; Santana, O. I.; Reyes-González, A.; Meza-Velázquez, J. A.; López-Calderon, M. J.; Domínguez-Martínez, P. A.; Maldonado-Jáquez, J. A.; Sánchez-Duarte, J. I. (Tropical Animal Science Journal, 2026)
Mesquite pods are traditionally used to feed livestock in arid regions. However, they are highly susceptible to beetle and other insect spoilage, so they must be preserved as silage for use during critical periods of feed scarcity. This study aims to assess the effects of increasing moisture levels from dry ground mesquite pods on fermentation parameters and nutrient composition of the silage as a method of preservation. The treatments consisted of adding 0%, 10%, 20%, 30%, 40%, and 50% water (w/w). Each treatment received four PVC mini silos under a completely randomized design. On average, each mini silo was filled with 1,325 g of ground mesquite pods for ensiling. All mini silos were stored at room temperature (17-22.5 °C) and opened after 40 days of fermentation. The treatments were compared by polynomial orthogonal contrasts. Fermentation results indicated that increasing the amount of added water reduced the pH (p = 0.003) and linearly increased lactic acid (p = 0.0002) in silage. Ammonia-N and the concentration of acetic and propionic acids had a quadratic effect (p = 0.004). Silage with 20-30% water had an intermediate pH (4.65-4.53) and lower ammonia-N levels (5.59-6.51). Losses of gas, effluent, and dry matter exhibited linear and quadratic effects (p0.05). However, neutral and acid detergent fiber increased both linearly (p